Studies on Agaricales of Kumaon Himalaya - ADHlKARI, R.S. (Indian Phytopathology, 2002)
Amanita xanthella and A. elata are recorded for the first time from India. The species are described from specimens collected during a survey of Agaricales conducted in the Kumaon Himalaya, and these descriptions are compared with the type descriptions.